THE TYPES OF QUESTIONS USED BY THE TEACHERS IN READING CLASS : A Case Study at MTs N Model Samarinda - Fitriana, Rahmawati (2010)
This study reports on the types of questions used by teachers in reading class at MTs N Model Samarinda. This study is intended to observe the types of questions used by the teachers of MTs N Model Samarinda, including, (1) the level of teachers' questions based on Barrett's Taxonomy, (2) the questioning strategies used, (3) the influence of those type of questions and questioning strategies used on the class interaction during the process of teaching reading. This study used descriptive qualitative research. The data were collected by conducting classroom observation and interview. The data were then analyzed and classified by using Barrett's Taxonomy and questioning strategies as a base reference, and also other theories which support this research. In reference to the findings, it showed that all participants applied only four of the five questions levels of Barrett's Taxonomy (Barrett, 1956, cited in Clymer,1968) successfully. They are literal, reorganization, inferential, and evaluative. The only one which was not applied by them, was appreciative level. It was due to the facts that their teaching experiences and their self-development motivation affected their competence in constructing types of questions. The questioning strategies (Jacobsen,at.al (1989:176), which consists of redirection, prompting, and probing, showed that all of them enabled to process those strategies in their reading instruction; however, the redirection is the most favorable used by the teachers. Meanwhile, concerning to the influence of those types of questions and questioning strategies, it was found that those types predisposed the ways of the teachers in posing and eliciting their questions to the students, and to assist the students' improvement strategies. Finally, it is suggested that the teachers of reading comprehension should improve not only their questioning skill but also should maintain the reading classroom interactions effectively by observing students' reactions to the teacher questions.